DO QUILOMBO À ESCOLA: RESISTÊNCIAS ANCESTRAIS NO ENSINO DE HISTÓRIA LOCAL - Jesus, Anaclecia Vieira de (2021)
This research seeks to discuss and problematize the erasure of the history of black people in the city, progressively denaturalizing the notion that important people and the great facts and events chosen by official speeches are the only paths for teaching. Aiming to carry out a historical study on the Quilombola Community of Nova Vista – São Mateus, ES, with special focus on the figure of Zé de Ana, King of Ticumbi and Master of the Cabula. The history of struggle and resistance of this community is presented. Through the methodology of oral history we seek support in the community's orality to record its history, knowledge, practices and identity elements. The writing was woven, in its theoretical framework, by authors such as: Bloch (2001), Ginzburg (1987), Benjamin (1986), Freire (1986), Lajolo and Zilberman (2007). The conclusion reached, through dialogues with the memories shared by community elders and teachers from schools located in quilombola territories in the municipality, is the possibility of teaching focused on the history of their place. In addition to the dissertation, as an integral part of the research, there is a paradidactic literary children's book entitled “O Reizinho de Nova Vista”, based on the narratives produced by the elders of the Nova Vista quilombola community, who resist the erasure of their history.